2014
DOI: 10.1007/s11434-014-0570-5
|View full text |Cite
|
Sign up to set email alerts
|

Big data resource service platform for the internet financial industry

Abstract: It is now the era of big data. Massive volumes of complex and dynamic data exist in a variety of industries, including internet finance. This paper briefly describes the current big data situation and its significance, discusses the big data resource service platform architecture that includes three levels: data resource identification and access, data resources storage and analysis, and network information service platform, and then introduces some work undertaken by our project team on big data analysis rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Xie and Zou (2012) found that the internet can significantly lower transaction costs, reduce information asymmetry, enhance the efficiency of risk-based pricing and risk management, and expand sets of feasible transactions. Internet finance received great attention from both academic studies and the financial industry due to its significant impact on the efficiency of financial activities (Wang et al, 2014). Fintech has played a crucial role in revolutionizing the financial services industry since its inception.…”
Section: Literature Review and Analysis Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie and Zou (2012) found that the internet can significantly lower transaction costs, reduce information asymmetry, enhance the efficiency of risk-based pricing and risk management, and expand sets of feasible transactions. Internet finance received great attention from both academic studies and the financial industry due to its significant impact on the efficiency of financial activities (Wang et al, 2014). Fintech has played a crucial role in revolutionizing the financial services industry since its inception.…”
Section: Literature Review and Analysis Of Related Workmentioning
confidence: 99%
“…Fintech has had a bad rap as a disruptive technology, but this study revealed that it offers the Saudi banking sector several advantages (Abdalmajeed et al, 2023). FinTech is now widely used in a variety of nations worldwide (Jiang et al, 2014). It is well known to be a 21 st -century financial product.…”
Section: Literature Review and Analysis Of Related Workmentioning
confidence: 99%
“…The big data platform mainly collects and processes data and realtime feedback to deal with huge amounts of structured data, semistructured data and unstructured data [11]. Big data platform will be combined with the currently very mature GIS technology, businessoriented, providing a variety of data support services.…”
Section: The Collision Between Insurance and Big Data 51 Big Data Plmentioning
confidence: 99%
“…Financial data has the characteristics of big data in time series. To perform real-time predictive analysis on financial big data, it is necessary to use the financial big data platform [5,6]. Literature [7] based on an in-depth study of the Tmall platform web page structure uses automated testing techniques to simulate the way people browse web pages and e-commerce platform search engines, effectively avoiding the limitations of anticrawling technology.…”
Section: Introductionmentioning
confidence: 99%